Rationale and Design for the Diabetes RElated to Acute Pancreatitis and Its Mechanisms Study: A Prospective Cohort Study From the Type 1 Diabetes in Acute Pancreatitis Consortium. Issue 6 (July 2022) - Hart, Phil A.; Papachristou, Georgios I.; Park, Walter G.; Dyer, Anne-Marie; Chinchilli, Vernon M.; Afghani, Elham; Akshintala, Venkata S.; Andersen, Dana K.; Buxbaum, James L.; Conwell, Darwin L.; Dungan, Kathleen M.; Easler, Jeffrey J.; et al.
Abstract: Acute pancreatitis (AP) is a disease characterized by an acute inflammatory phase followed by a convalescent phase. Diabetes mellitus (DM) was historically felt to be a transient phenomenon related to acute inflammation; however, it is increasingly recognized as an important late and chronic complication. There are several challenges that have prevented precisely determining the incidence rate of DM after AP and understanding the underlying mechanisms. The DREAM (Diabetes RElated to Acute Pancreatitis and its Mechanisms) Study is a prospective cohort study designed to address these and other knowledge gaps to provide the evidence needed to screen for, prevent, and treat DM after AP. In the following article, we summarize literature regarding the epidemiology of DM after AP and provide the rationale and an overview of the DREAM study.